Komunikacyjna rola przedogródka, czyli rzecz o ludowej wizji świata - Grzegorzewska, Anita (Strategie komunikacyjne i procesy twórcze, 2022)
Among the studies on the aspects of communication understood as the transfer of information (meanings), there are no works that discuss the communicative potential of nature. The author, referring to the methodological assumptions developed within communicativism, offers the concept of folk communicative competence. The proposed model of folk communicative competence, including the acts: plant (human) - human and plant (supernatural power / folk faith), allows to define the role of vegetation from the traditional backyard garden in the way of thinking and functioning of the rural community. The author prooves that the front gardens were not only an important element of material culture, but they were also connected with the sphere of spiritual culture.